Professional Attitudes Toward the Use of Denture Adhesives: A Survey among Nepalese Prosthodontists (Nepal Medical College Journal, 2020)
The dental profession has been slow to accept denture adhesive (DA) as a means to enhance denture retention and function which has produced conflicting views both in clinical practice and dental education. Many practitioners view adhesive usage as a reflection of lack of prosthetic expertise and poor clinical skills. A survey was conducted among Nepalese Prosthodontists to explore their attitudes towards DAs. A pre-tested, self-administered anonymous questionnaire consisting of 12 close-ended questions was mailed to the participants. Among all the respondents, 91.7% used DA as a beneficial adjunct to stabilize trial bases in the early stages of denture fabrication. However, only 41.3% of prosthodontists prescribed DA for routine denture patients. Majority of respondents prescribed powder form of adhesives (96.7%). Respondents believed that denture adhesives were helpful in stabilizing trial bases in the early stages of denture fabrication (80%), enhanced the fit of the prosthesis (81.7%) and provided psychologic comfort to the patient (91.7%). They agreed that denture adhesives have the potential to mask pathological tissue changes under ill-fitting dentures (65 %), to permit avoidance of good clinical practice (45%), and to contribute to patients not seeing a dentist for regular follow up visits (61.7%). It was concluded that DAs are a beneficial adjunct to the dentist in the fabrication of dentures. However, enough cautions are required for preventing potential misuses of DAs, by both dentists and patients. The efficient way to optimize the beneficial aspects of DA depends on its rational, selective, and supervised usage.